Genomewide Association Study Identifies Cxcl Family Members as Partial Mediators of LPS‐Induced Periodontitis. (22nd May 2018) - Hiyari, Sarah; Green, Elissa; Pan, Calvin; Lari, Soma; Davar, Mina; Davis, Richard; Camargo, Paulo M; Tetradis, Sotirios; Lusis, Aldons J; Pirih, Flavia Q
ABSTRACT: Periodontitis (PD) is characterized by bacterial infection and inflammation of tooth‐supporting structures and can lead to tooth loss. PD affects ∼47% of the US population over age 30 years and has a heritability of about 50%. Although the host immunoinflammatory response and genetic background play a role, little is known of the underlying genetic factors. We examined natural genetic variation in lipopolysaccharide (LPS)‐induced PD across a panel of inbred mouse strains, the hybrid mouse diversity panel (HMDP). We observed a strain‐dependent sixfold difference in LPS‐induced bone loss across the HMDP with a heritability of 53%. We performed a genomewide association study (GWAS) using FAST‐LMM, which corrects for population structure, and identified loci significantly associated with PD. We examined candidate genes at a locus on chromosome 5, which suggested a relationship between LPS‐induced bone loss and, together with expression data, identified Cxcl family members as associated with PD. We observed an increase in Cxcl10 protein, as well as immune cells and pro‐inflammatory cytokines in C57BL/6J (high bone loss strain) but not in A/J (low bone loss strain) after LPS injections. Genetic deletion of CXCR3 (Cxcl9 and10 receptor) demonstrated a ∼50% reduction in bone loss and reduced osteoclasts after LPS injections. Furthermore, WT mice treated with AMG‐487 (a CXCR3 antagonist) showed a ∼45% reduction in bone loss and decreased osteoclasts after LPS injections. We conclude that CXCR3 is a strong candidate for modulating the host response in individuals susceptible to PD. © 2018 American Society for Bone and Mineral Research.